International Companion to Edwin Morgan - Riach, Alan, 1957- (International companions to Scottish literature., 2015)
Edwin Morgan (1920-2010) is one of the giants of modern poetry. Scotland's national poet from 2004 to his death in 2010, in his long life he produced an incredible range of work, from the playful to the profound. This INTERNATIONAL COMPANION gives a comprehensive overview of Morgan's poetry and drama. A range of expert contributors guide the reader along Morgan's astonishing, multi-faceted trajectory through space and time, and provide students with an essential and accessible general introduction to his life and work.